Pengaruh Pre-Treatment Kimia dan Biologi Terhadap Produksi Biogas dari Kulit Kopi - Dennis Farina Nury; Muhammad Zulfikar Luthfi; Ahmad Rifqiyan Farohi; Tri Widjaja (Politeknik ATI Padang, 2023)
Coffee, as a major commodity in Indonesia, produces a huge number of byproducts and residues during the processing process. Coffee wastes and byproducts produced during coffee berry processing are a major source of contamination and represent significant environmental challenges in the coffee production process. One promising alternative in utilizing coffee wastes is converting into energy source i.e, of biogas from coffee pulp. Coffee pulp has toxic components that act as a methane inhibitor; these type of biomass have a problem with the lignin degradation process, which binds cellulose and hemicellulose. The use of cow's rumen fluid for methane production from coffee pulp is still rare, particularly for rumen fluid. Chemical pretreatment was carried out using alkali-peroxide followed by rumen fluid pretreatment. The performance of biogas produced from coffee pulp (with and without pretreatment) using rumen fluid as an inoculum has been investigated. Biogas was produced in a semi-batch reactor with a working volume of 2 liters for 30 days. Removal lignin, SS, VFA, and biogas yield were measured. This study aims to determine the biogas production from coffee pulp using variation HRT 20 and 30 days. It can be concluded that chemical pretreatment of NaOH - H2O2 combination can reduce lignin up to 75.02%. The volume of biogas produced increased with chemical pretreatment and rumen fluid as compared to the substrate with only rumen pretreatment According to Gas Chromatography analysis, the methane gas obtained from chemical pretreatment and rumen with HRT 30 days is 47.93%, while the methane obtained from rumen pretreatment with HRT 30 days is 34.28%.